NSRG-05. SAFETY OF ULTRASOUND-INDUCED BLOOD-BRAIN BARRIER OPENING IN PEDIATRIC PATIENTS WITH REFRACTORY SUS-TENTORIAL MALIGNANT BRAIN TUMORS BEFORE CHEMOTHERAPY ADMINISTRATION – THE SONOKID CLINICAL TRIAL. Issue 2 (22nd June 2018) - Beccaria, K; Canney, M; Bouchoux, G; Zohar, S; Boddaert, N; Bourdeaut, F; Doz, F; Dufour, C; Grill, J; Carpentier, A; Puget, S
Abstract: OBJECTIVE: To determine the safety of repeated disruption of the blood-brain barrier (BBB) by low intensity pulsed ultrasound (LIPU) with the Sonocloud ® device in children with recurrent malignant supra-tentorial brain tumors prior to intra-venous carboplatin chemotherapy. The safety of this procedure is currently being validated in adult patients with recurrent glioblastoma (Carpentier et al. 2016). MATERIAL AND METHODS: This single-center phase I/IIa clinical trial will include 12 to 24 patients aged 5 to 18 years, with recurrent malignant supra-tentorial brain tumors. The Sonocloud ® device will be implanted into the skull under general anesthesia, during a standard procedure (biopsy or resection). Thanks to a transdermic connexion, sonications will be performed monthly in combination with injection of an ultrasound contrast agent (Sonovue ® ). US parameters will be based on the adult patients study. BBB disruption will be evaluated using multimodal magnetic resonance imaging (MRI). Carboplatin will be injected during the hour following the sonication. Patients will receive a maximum of 6 monthly sonications and will be followed at least for 6 months after the last sonication. EXPECTED RESULTS: The principal criteria will be the absence of grade ≥ 3 neurological toxicity (NCI-CTCAE 4.0 Version, clinical and radiological assessment) linked to the US-induced opening of the BBB after first treatment. Secondary evaluation criterias will include tolerance of repeated sonications, overall survival and progression-free survival, and feasibility of the technique. CONCLUSION: SONOKID is the first clinical trial assessing the feasibility and tolerance of US-induced opening of the BBB in children. SPONSOR Canceropole Ile de France.